Contactin 1 IgG4 associates to chronic inflammatory demyelinating polyneuropathy with sensory ataxia - Miura, Yumako; Devaux, Jérôme J.; Fukami, Yuki; Manso, Constance; Belghazi, Maya; Wong, Anna Hiu Yi; Yuki, Nobuhiro (Brain (London, England : 1878), 2015)
A Spanish group recently reported that four patients with chronic inflammatory demyelinating polyneuropathy carrying IgG4 autoantibodies against contactin 1 showed aggressive symptom onset and poor response to intravenous immunoglobulin. We aimed to describe the clinical and serological features of Japanese chronic inflammatory demyelinating polyneuropathy patients displaying the anti-contactin 1 antibodies. Thirteen of 533 (2.4%) patients with chronic inflammatory demyelinating polyneuropathy had anti-contactin 1 IgG4 whereas neither patients from disease or normal control subjects did (P = 0.02). Three of 13 (23%) patients showed subacute symptom onset, but all of the patients presented with sensory ataxia. Six of 10 (60%) anti-contactin 1 antibody-positive patients had poor response to intravenous immunoglobulin, whereas 8 of 11 (73%) antibody-positive patients had good response to corticosteroids. Anti-contactin 1 IgG4 antibodies are a possible biomarker to guide treatment option.